Mitochondrial phosphoenolpyruvate carboxykinase (PEPCK-M/PCK2), phosphoglycerate dehydrogenase (PHGDH) and muscle cell growth - Brearley, Madelaine C. (2018)
Our group reported upregulation of a novel group of genes was associated with beta-adrenergic agonist (BA)-induced muscle hypertrophy in pigs. The aim of this PhD was to investigate the expression of these genes, and particularly the role of mitochondrial phosphoenolpyruvate carboxykinase (PEPCK-M/PCK2) and phosphoglycerate dehydrogenase (PHGDH), in muscle cell growth. A significant (p<0.01) increase in mRNA transcript abundance was detected at day 2 of differentiation in C2C12 cells for PEPCK-M, PHGDH, phosphoserine aminotransferase-1, phosphoserine phosphatase, asparagine synthetase, sestrin-2 and activating transcription factor-5. This novel peak coincided with the peak in myogenin mRNA, connecting these genes with a crucial point of myogenic differentiation. Hypertrophy was induced in C2C12 myotubes treated with dibutyryl-cAMP (dbcAMP), mimicking the BA response in vivo, however mRNA expression of these genes were unaffected. The porcine myosin heavy chain (MyHC)-IIB promoter-reporter C2C12 cell assay demonstrated similar in vivo responses to known anabolic and catabolic agents. Thus, C2C12 cells were utilised to determine the role of PEPCK-M and PHGDH in myogenic differentiation. Firstly, C2C12 cells were treated with a PEPCK inhibitor, 3-Mercaptopicolinic acid (3-MPA). 3-MPA induced differentiation, resulting in a hypertrophic response comparable to dbcAMP treatment. However, it was unclear whether 3-MPA inhibited PEPCK-M enzyme activity as 3-MPA interfered with the in vitro assay. Next, C2C12 cells were transfected with either PCK2 or PHGDH overexpression construct. No obvious phenotype was observed, but PHGDH and PEPCK-M overexpression both increased MyHC-IIB mRNA. The reoccurring induction of the same group of genes along with MyHC-IIB supports the hypothesis that co-ordinated upregulation of these genes may drive hypertrophic growth. To conclude, PEPCK-M, along with other genes upregulated with BA-induced hypertrophy and C2C12 differentiation, show co-ordinate regulation in times of high biosynthetic demand. PEPCK-M appears to sit at an intersection that allows metabolic flux to be largely altered by diverting intermediates during energy metabolism.